The Effect of Leadership Style and Work Motivation on the Performance of Islamic Boarding School Employees - Annisa Nurul Bariroh; Kamila Syahra Maulida; Muhamad Alwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study seeks to determine how employee performance at Pesantren Al Ishlah Tajug is influenced by leadership style and work motivation. Descriptive correlation research using quantitative techniques is the methodology used in this study. All 30 employees of Pesantren Al Ishlah Tajug constituted the study population, which was selected using a direct random sampling technique. Employee performance, work motivation, and leadership style questionnaires provided the data. Multiple linear regression analysis is the method used to analyze the data in this study. Based on the results of Multiple Linear Regression analysis with t-test and F-test, this study concluded that employee performance is influenced by leadership style in the Al Ishlah Tajug Islamic Boarding School environment. Work motivation affects the performance of employees of Al Ishlah Tajug Islamic Boarding School. Work motivation and leadership style affect the performance of employees of Al Ishlah Tajug Islamic Boarding School. Leadership style and work motivation affect the performance of staff at Al Ishlah Tajug Islamic Boarding School by 57.4%.